Decision Support System Selection of Achievement Employees in PT PLN (PERSERO) UP3 Samarinda using Simple Multi-Attribute Rating Technique (SMART) Method - Ita Arfyanti; Ekawati Yulsilviana; Muhammad Iqbal (TEPIAN, 2021)
The purpose of this research is to produce a Decision Support System for Selection of Outstanding Employees at PT PLN (Persero) UP3 Samarinda by using the SMART (Simple Multi Attribute Rating Technique) method with the hope that the selection will be carried out objectively. By using the PHP programming language and the database used is MySQL. In this study, the data collection techniques used were literature study, observation and interviews. The decision support system for selecting outstanding employees at PT PLN (Persero) UP3 Samarinda, is a system designed to assist in making decisions in selecting the right outstanding employees using the help of the SMART method, using the feasibility study system development stage, designing, selecting and making a support system. Decision. The result of this research is the creation of a decision support system to make decisions for high performing employees. Users can input employee data, criteria data and sub criteria data. Then the system will look for a solution using the SMART (Simple Multi Attribute Rating Technique) method. After the decision is obtained, the system will display the decision